Prenatal dexamethasone exposure and the risk of early-onset sepsis in preterm infants - Yang, Yulu (Frontiers in Pediatrics, 2025)
BackgroundRobust evidence has consistently demonstrated the impact of antenatal corticosteroid (ACS) administration on reducing mortality and improving short-term neonatal outcomes in singleton preterm infants. However, its effect on neonatal sepsis, particularly early-onset sepsis (EOS), remains poorly understood and requires further investigation. This study aimed to evaluate the potential association between prenatal dexamethasone exposure (PDE) and incidence of EOS in preterm infants.MethodsThis retrospective, single-center observational study included singleton preterm neonates with a gestational age less than 32 weeks or a birth weight below 1,500 g between 2022 and 2024. Participates were stratified into four groups based on PDE: no PDE, partial PDE (1–3 doses), PDE 1–7 days (complete course with delivery within 7 days of administration), and PDE ≥8 days (complete course with delivery more than 7 days after administration). The primary outcome was the incidence of EOS, while secondary outcomes encompassed other short-term neonatal complications.ResultsThe analysis revealed that neonates in the PDE 1–7 days group demonstrated a significantly reduced incidence of EOS compared with the no PDE group [adjusted odds ratio[aOR]: 0.299, 95% confidence interval [95%CI]: 0.122–0.731]. Furthermore, this group exhibited superior outcomes, including lower rates of respiratory distress syndrome (RDS), reduced the need for surfactant treated in RDS cases, and decreased extrauterine growth restriction (EUGR). Notably, the PDE ≥8 days group was associated with an elevated risk of EOS when compared with the PDE 1–7 days group.ConclusionPDE, particularly when a complete course is administered 1–7 days prior to delivery, demonstrates a significant protective effect against EOS in preterm infants. Nevertheless, large-scale multicenter prospective studies are warranted to further validated these findings and to comprehensively evaluate the long-term neurodevelopmental and systemic outcomes associated with PDE administration.